Xylanase inhibition by the derivatives of lignocellulosic material. (March 2020) - Maulana Hidayatullah, Ibnu; Setiadi, Tjandra; Tri Ari Penia Kresnowati, Made; Boopathy, Ramaraj
Graphical abstract: Highlights: Effect of inhibitors on the xylanase activity was studied. Furans, aliphatic acids, and fermentation products were evaluated. Ethanol, vanillin, and formic acid showed the highest inhibition effect on xylanase. Ethanol competed with xylanase competitively. Vanillin showed uncompetitive inhibition. Abstract: Hydrolysis of lignocellulosic materials into simple sugar plays an important role in biorefinery. Hemicellulosic sugars from the hydrolysis of lignocellulosic materials could be used in xylitol production. However, xylanase activity during hydrolysis process is affected by activators and inhibitors that may present in the reaction system. The pretreatment process was reported to produce compounds that may affect the enzymatic hydrolysis process, such as furans, aliphatic acid, and aromatics. The purpose of this study was to investigate the inhibition effect of these potential inhibitors on xylanase activity. Three groups of potential inhibitors were evaluated including, furan, aliphatic acid, and hydrolysis-fermentation products. The result showed that ethanol, vanillin, and formic acid gave the highest inhibition effect from each group. Ethanol competed with xylanase competitively. Vanillin showed non-competitive inhibition. Formic acid performed mixed-inhibition by reducing maximum hydrolysis rate and giving varied Michaelis constant values at different concentrations.